DIGITAL TRADE AS AN IMPETUS FOR NEW REGULATORY INITIATIVES (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2019)
Digital technologies are affecting all types of global flows, including trade and migration flows, thus reducing spatial, temporal and cost barriers. Digital trade is an important part of these new global trends, supporting and changing the globalization process. The main aim of this paper is to identify key challenges in regulating and governing digital trade on different levels, as each level of governance encounters specific challenges. The contribution of the paper is twofold. First, it gives an overview of key digital trade regulatory issues at the national, regional and global level. Second, some specifics of digital trade are explored with the purpose of gaining a broader understanding of the need for new, or at least modified trading rules that would support digital trade and the digital economy.